Interstreet crossing issues in single-row routing - Salleh, Shaharuddin (2006)
In single-row routing, doglegs or the inter-street crossings, is an issue that greatly determines the congestion level in the printed-eircuit board (PCB) layout. A single-row network consists of a set of nets fonned from pairs of pins. The nets make up the wires in the PCB which are drawn from left to right in a non-erossing manner. In this scenario, the nets can be modeled as nodes in a planar graph. However, inter-street crossings in the node axis are allowed, and they are necessary to prevent the nets from crossing each other. Each inter-street crossing in the node axis creates a dogleg. A good PCB design requires evenly distributed doglegs that utilize the compact space to the maximum. Uneven distribution of doglegs may trigger technical glitches on the PCB such as the creation of electric and magnetic fields. In this paper, we discuss this issue and a technique for distributing the doglegs evenly in the pin intervals.